Mechanism of photoanodes for dye-sensitized and perovskite solar cells - Low F.W.; Mahalingam S.; Shakeri M.; Yaw C.T.; Samsudin N.A.; Amin N.; Tiong S.K.; Goh S.M.; Manap A.; Hen C.K.; Pasupuleti J. (Springer Science and Business Media Deutschland GmbH, 2023)
The demand for fossil fuel consumption is continuously increasing due to the growth of the worlds population. Carbon dioxide (CO2) gas emission from conventional energy sources eventually will amplify the Earths natural greenhouse effect and hence will result in global warming. Therefore, to reduce the risk of climate change, photovoltaic solar cell (PV) devices have been developed. Surprisingly, PV system has capability to conduct useful electricity from natural sunlight source, which provides clean, sustainable, and renewable energy instead of combusted conventional fossil fuel sources. Nowadays, both dye-sensitized cells (DSSCs) and perovskite solar cells (PSCs) were investigated more intensively than the first- and second-generation solar cell systems due to their flexibility, transparency, and lighter weight materials. In fact, photoanode elements played an essential role in determining the strength of light-harvesting absorption and generating excited electron charge carriers mobility between dye/perovskite and respective transparent conductive oxide (TCO) glasses. Apart from that, binary/ternary transition metal oxide material selection (TiO2, ZnO, SnO2, MgO, WO3, etc.) of photoanode in DSSCs and PSCs is also a crucial factor for photogenerated electrons. However, still metal oxide materials have some drawbacks such as high recombination rate which resulted in losses of overall photoenergy conversion efficiency (PCE) performance. In fact, the PCE of existing either DSSC or PSC devices still have rooms to improve compared to first- and second-generation solar cells. This chapter briefly discussed the operational principle, material selection, key problems, and also the insight to commercialization of organic PV devices. 2020, Springer Nature Switzerland AG.